The Importance of Digital-Based Secondary Education Transformation at SMPN 1 Mataram - Hawa Sadidha Afikry; M. Yusuf Zakaria (Penerbit Presisi Pustaka, 2026)
The transformation of secondary education into a digital school has become an urgent need in this era of rapid technological development. This article aims to examine the importance of school digitalization in improving the quality of learning, expanding educational access, and preparing students to face the demands of the 21st century. The article's significance lies in its contribution to understanding how the integration of digital technology can create a more effective, adaptive, and inclusive learning environment. Furthermore, this article offers insights into the role of digital platforms, technological literacy, and learning management systems in supporting interactive and collaborative learning processes that are relevant to the needs of the times. The research method used is a literature review, reviewing various credible academic sources to analyze the concept of digital schools, their implementation challenges, and development strategies. Through this approach, this article compiles a systematic analysis of policy developments, infrastructure, and educator readiness in implementing school digitalization. The study results show that digital transformation in secondary education not only impacts the quality of learning but also strengthens the digital competence of students and teachers. This article emphasizes that the success of digital schools requires adequate infrastructure support, strengthening digital literacy, and updating relevant curricula to prepare the younger generation to face global dynamics and the future world of work.